Dimerization of α1-adrenoceptors. (26th October 2004) - Milligan, G.; Pediani, J.; Fidock, M.; López-Giménez, J.F.
Abstract : Three distinct genes encode α1 -adrenoceptors. Although homodimers of each subtype have been reported, certain but not all combinations of heterodimers of the α1 -adrenoceptors appear to form. Key studies in this field are reviewed and the approaches that have been applied to monitoring the selectivity and the basis of α1 -adrenoceptor dimerization are discussed.